SIMULTANEOUS METHOD DEVELOPMENT AND VALIDATION OF COMBINED DOSAGE FORM DAPAGLIFLOZIN AND VILDAGLIPTIN IN BULK AND COMBINED TABLET DOSAGE FORM BY UV SPECTROPHOTOMETER - K, BHAVYA SRI; M, NANDHINI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: In the present work on the determination of dapagliflozin and vildagliptin in tablet dosage form, a simple, rapid, inexpensive, accurate, and precise stability-indicating ultraviolet (UV) method was established. For the measurement of vildagliptin and dapagliflozin in tablet dosage form. Methods: A UV-visible spectrophotometric technique was done. Double-distilled water was used as the dapagliflozin’s diluent. Vildagliptin’s diluent was 0.1 N NaOH. The diluent used in the dosage form that contains both vildagliptin and dapagliflozin was 0.1 N NaOH. This approach was verified for linearity, accuracy, precision, QL, and detection limit (DL). Results: For the dosages of dapagliflozin and vildagliptin (0.16:1.6–2.2:22 μg/mL), linearity were seen. Vildagliptin and dapagliflozin were found to have QLs of 3.7432 μg/mL and 1.2860 μg/mL, respectively. Vildagliptin and dapagliflozin were found to have DLs of 1.2352 and 0.4244, respectively. The developed method for estimating the dosage of dapagliflozin and vildagliptin in tablet form was proven to be accurate, exact, and quick. Under identical circumstances, the medication was stressed by hydrolysis, oxidation, photolysis, and thermal deterioration. The UV-visible system was used to analyze the stress sample. Conclusion: The proposed method was found to be simple, precise, accurate, and reproducible and can be used for routine analysis of dapagliflozin and vildagliptin in bulk and tablet dosage forms.